Rural tourism demand model of international visitors to the Kilim Karst Geoforest Park, Langkawi - Matthew, Nitanan Koshy; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (Faculty of Forestry, Universiti Putra Malaysia, 2013)
The existence of pristine natural resources in rural areas is important for the rural tourism development. Kilim Karst Geoforest Park in Langkawi offers rural tourist attractions to visitors. The rural tourism demand of international visitors to the site can be estimated using the Travel Cost Method (TCM). The objectives of this study were to develop the rural tourism demand model and to compare the consumer surplus (CS) value for both the travel cost to Langkawi and Kilim models. Structured questionnaires and face-to-face data collection methods were employed to obtain the primary data from 330 international visitors using the convenient sampling technique. A Poisson regression analysis was conducted to estimate the individual Travel Cost Method (ITCM) model using the Limited Dependent models (LIMDEP) software version 4. The findings showed that the CS value, per trip, for the Langkawi model is € 6993 which is greater than the Kilim models (€ 1437 and € 633).